Phylogenetic Diversity of Urban Floras in the Central Urals - Tretyakova, Alyona S.; Yakimov, Basil N.; Kondratkov, Pavel V.; Grudanov, Nickolay Yu.; Cadotte, Marc W. (Frontiers in Ecology and Evolution, 2021)
Modern cities harbor a high diversity of plants and urban floras are significantly different from natural floras especially when considering the proportion of alien species found in cities. These floras harbor a high diversity species but it is not clear whether urban areas disproportionately select for species from relatively few evolutionary lineages or provide opportunities for species across the full spectrum of plant lineages. Here we examined the taxonomic and phylogenetic diversity of the floras in four cities (Yekaterinburg, Kamensk-Uralsky, Krasnoufimsk, Turinsk) in the understudied region of Central Urals (Russian Federation). We classified native species into indigenous and apophytic species, namely those that are sensitive to anthropogenic disturbance and those that have expanded their range with human activity, respectively. Alien species were classified into archaeophytes and neophytes according to when they were introduced (i.e., before or after than 1800). Phylogenetic diversity was quantified using Faith’s index to reflect total evolutionary history in urban areas and mean phylogenetic distance, MPD, to reflect species dissimilarity. Phylogenetic diversity of native species was higher than that for alien species, and the standardized effect size of MPD for natives was positive, reflecting their general dissimilarity from one another, while it was very negative for aliens, showing that they were phylogenetically clustered. However, among natives, apophytes were significantly clustered, while indigenous species were overdispersed. For the aliens, MPD was higher for archaeophytes compared to neophytes, though both groups were significantly clustered. These results show that urbanization leads to a non-random selection of plants. Apophytes and alien plants were comprised of closely related species, reflecting similar ecological traits and are likely to be pre-adapted to the environmentally altered and highly disturbed urban environment.